Peningkatan Pemahaman Sistem Informasi Penjualan bagi Pelaku Usaha Lokal di Desa Baduy untuk Mendukung Pemasaran Produk Tradisional (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2026)
This community service activity aims to enhance the understanding of local business actors in Kanekes Village (Baduy Luar) regarding the implementation of a sales information system to support the management and marketing of traditional handicraft products. The main problems faced by partners include unstructured transaction recording, low utilization of sales data, and business management that is still based on memory. The implementation method uses a participatory approach through socialization, training, hands-on practice, and mentoring, with data collection techniques carried out through interviews and field observations. The activity was conducted on April 17, 2026, involving MSME handicraft actors as the main partners. The results show an increase in business actors’ understanding of the importance of sales recording systems as a basis for business management. Participants began to be able to record transactions in a more structured and simple manner and utilize sales data to monitor business performance and identify the most in-demand products. In addition, there was a shift in business management patterns from memory-based to simple data-based systems. This activity also encouraged improvements in digital literacy through the introduction of social media utilization and digital marketing strategies. Overall, this program contributes to strengthening the capacity of business actors and supporting the more effective and sustainable development of traditional product marketing. Keywords: Community Service, Msmes, Sales Information System, Baduy Luar, Digital Marketing